The sufficient minimal set of miRNA seed types - Ellwanger, Daniel C.; Büttner, Florian A.; Mewes, Hans-Werner; Stümpflen, Volker (Bioinformatics (Oxford, England), 2011)
Motivation: Pairing between the target sequence and the 6–8 nt long seed sequence of the miRNA presents the most important feature for miRNA target site prediction. Novel high-throughput technologies such as Argonaute HITS-CLIP afford meanwhile a detailed study of miRNA:mRNA duplices. These interaction maps enable a first discrimination between functional and non-functional target sites in a bulky fashion. Prediction algorithms apply different seed paradigms to identify miRNA target sites. Therefore, a quantitative assessment of miRNA target site prediction is of major interest. Results: We identified a set of canonical seed types based on a transcriptome wide analysis of experimentally verified functional target sites. We confirmed the specificity of long seeds but we found that the majority of functional target sites are formed by less specific seeds of only 6 nt indicating a crucial role of this type. A substantial fraction of genuine target sites arenon-conserved. Moreover, the majority of functional sites remain uncovered by common prediction methods. Contact:  florian.buettner@helmholtz-muenchen.de  v.stuempflen@helmholtz-muenchen.de Supplementary Information:  Supplementary data are available at Bioinformatics online.